ASSESSMENT OF THE ENVIRONMENTAL POLLUTION DETERMINANTS IN THE ECONOMY SECTORS OF LITHUANIA - Astrida Miceikienė; Daiva Rimkuvienė; Kristina Gesevičienė (Copernican Journal of Finance & Accounting, 2020)
The research provides substantiation for the problem of environmental pollution in Lithuania on the basis of the increase in the greenhouse gas (GHG) emissions in the country’s individual economy sectors. The research aims at assessing the GHG emissions of individual sectors of economic activities with reference to the key economic indicators of the respective sectors. The performed analysis of the GHG emissions and their determinants in Lithuania has not shown any common trends in GHG emissions and determining factors among the economic activities. The environmental taxes do not perform the goals set for these taxes, while investments into environmental protection have generated a positive effect only in the economic activities of water supply; sewerage, waste management and remediation. The relationship between GDP and GHG emissions is significant for certain economic activities only.